Cognitive chicken or the emotional egg? How reconceptualizing decision-making by integrating cognition and emotion can improve task psychometrics and clinical utility - Buelow, Melissa T.; Moore, Sammy; Kowalsky, Jennifer M.; Okdie, Bradley M. (Frontiers in Psychology, 2023)
Decision-making is an executive function, tapping into cognitive, emotional, and personality-based components. This complexity, and the varying operational definitions of the construct, is reflected in the rich array of behavioral decision-making tasks available for use in research and clinical settings. In many cases, these tasks are "subfield-specific," with tasks developed by cognitive psychologists focusing on cognitive aspects of decision-making and tasks developed by clinical psychologists focusing on interactions between emotional and cognitive aspects. Critically, performance across different tasks does not consistently correlate, obfuscating the ability to compare scores between measures and detect changes over time. Differing theories as to what cognitive and/or emotional aspects affect decision-making likely contribute to this lack of consistency across measures. The low criterion-related validity amongst decision-making tasks and lack of consistent measurement of the construct presents challenges for emotion and decision-making scholars. In this perspective, we provide several recommendations for the field: a) assess decision-making as a specific cognitive ability versus a taxonomy of cognitive abilities; b) a renewed focus on convergent validity across tasks; c) further assessment of test-retest reliability versus practice effects on tasks; and d) reimagine future decision-making research to consider the research versus clinical implications. We discuss one example of decision-making research applied to clinical settings, acquired brain injury recovery, to demonstrate how some of these concerns and recommendations can affect the ability to track changes in decision-making across time.